New Strategies for the Treatment of Atrial Fibrillation - Norbert Jost; Torsten Christ; János Magyar (MDPI AG, 2021)
Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia in the clinical practice. It significantly contributes to the morbidity and mortality of the elderly population. Over the past 25-30 years intense effort in basic research has advanced the understanding of the relationship between the pathophysiology of AF and atrial remodelling. Nowadays it is clear that the various forms of atrial remodelling (electrical, contractile and structural) play crucial role in initiating and maintaining the persistent and permanent types of AF. Unlike in ventricular fibrillation, in AF rapid ectopic firing originating from pulmonary veins and re-entry mechanism may induce and maintain (due to atrial remodelling) this complex cardiac arrhythmia. The present review presents and discusses in detail the latest knowledge on the role of remodelling in AF. Special attention is paid to novel concepts and pharmacological targets presumably relevant to the drug treatment of atrial fibrillation.